Accessing Multimedia Technology and Listening Skill: Are they correlated? - Yana, Dewi; Putri, Aulia (Proceeding of International Conference on Language Pedagogy (ICOLP), 2021)
People’s lives are affected by several aspects of Information, Communication, and Technology, and multimedia technology is one of them. Then, Junior-senior-higher students today are identified as generation Z; they are characterized by the first digital generation who love to access the internet. This paper presents the correlation between students’ intensity of accessing multimedia technology products via the internet toward their listening skills. This study applies a quantitative method with a correlational design. The population is the first year’s students of the English Education Study Program of UNRIKA which applies the total sampling technique. The research data were gathered from an online questionnaire and listening test. The data were analyzed with descriptive statistics- Pearson correlation employing SPSS to determine the correlation between; students’ intensity of accessing multimedia technology (MT) products through the internet and listening skill. The result found that there is a moderate and negative correlation between the two variables (the Pearson correlation value is -0.252 > 0.05). There are some possible factors considered to the finding; it implies seeking further truth of the factors considered.